Kant and atheism: The notion of «doctrinal belief» in the «Canon» of the «Critique of pure reason» - Olesti Vila, Josep (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
This article deals with the third section of the «Canon» of the Critique of Pure Reason, dedicated to the distinction between opinion, knowledge and belief, to analyze the concept of «doctrinal belief» (doctrinaler Glaube), which does not appear explicitly in any other place of the Kantian corpus. It is argued that this concept, under which Kant subsumes our belief in the existence of God, is designed to discard so-called default atheism (or the presumption of atheism), which would otherwise obtain primacy in critical epistemolgy.